The Effect of Compost and Phonska Fertilizer on the Growth and Yield of Sweet Corn (Zea mays saccharata) Varieties of Bonanza. - Lafina, Salmah; Napitupulu, Marisi (Universitas 17 Agustus 1945 Samarinda, 2018)
Effect of Compost AndPhonskaTerhadap Fertilizer Plant Growth and Results Sweet Corn (Zea mays saccharata) Varieties Bonanza.The research aims to; determine the effect of compost and fertilizer PhonskaTerhadap Growth And Crop Sweet Corn (Zea mays saccharata) Varieties Bonanza. This study was conducted from April to June 2015, starting from site preparation to harvest. Place the District Education Research Road Teluk Lingga North Sangatta East Kutai. The method used in this study using a randomized block design (RAK) with 2 Factorial and each treatment was repeated 3 times. The treatment is factor 1: compost (K) with 4 levels of treatment are: k0 = no application of compost fertilizer (control), k1 = compost 10 tons / ha, equivalent to 2.53 kg / plot, k2 = compost 20 tons / ha equivalent with 5.06 kg / plot, k3 = compost 30 tons / ha, equivalent to 7.59 kg / plot. Factor 2: NPK fertilizer phonska (P) with 4 levels of treatment are: p0 = without fertilizer phonska (control), p1 = fertilizer phonska 400 kg / ha equivalent to 6,325 g / plant, p2 = fertilizer phonska 450 kg / ha equivalent to 7.906 gram / plant, p3 = fertilizer phonska 500 kg / ha equivalent to 9.487 g / plantAnalysis of data using tables of analysis of variance (ANOVA) with further testing Least Significant Difference (LSD) level of 5%. Parameters used; Plant height (cm) 20 DAT, DAT 30, 40 HST and 50 HST, 2. Age exit male flowers (day), age exit female flowers (days) Total cob crop (fruit), cob diameter (cm), Weight ear cropping (g), fruit Productivity (ton / ha).Results of analysis of variance showed that the interaction effect between compost and fertilizer npkPhonska not differ significantly affected the plant height 30 days after planting, 40 days after planting, 50 days after planting, the male flowers, female flowers, the number of cob, cob productivity. This is because the compost and fertilizer npkPhonska not influence.